2010
DOI: 10.1194/jlr.m007815
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal wall triglyceride concentration of morbidly obese persons is lower in those with type 2 diabetes mellitus

Abstract: This article is available online at http://www.jlr.orgThe insulin-resistance state and type 2 diabetes mellitus (T2DM) are closely related with an increase in cardiovascular disease. Factors conditioning this increase in cardiovascular disease include metabolic dyslipidemia associated with insulin resistance. It has recently been suggested that the overproduction of intestinally derived apolipoprotein (apo)B48-containing lipoproteins may contribute greatly to the dyslipidemia found in both the fasting and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…26 At the same time, the results of the expression of intestinal MTTP are contradictory. A previous study conducted in humans showed no significant changes in intestinal MTTP expression in morbidly obese subjects with T2DM, 3 whereas other studies show that there is an increase in intestinal MTTP expression in a rabbit model of diabetes 27 and in insulin-resistant non-diabetic Zucker obese fa/fa rats. 28 However, there is little information regarding MTTP in humans.…”
Section: (Fas) (F) Apolipoprotein A-iv (Apo A-iv) (G) Diacylglyceromentioning
confidence: 88%
See 4 more Smart Citations
“…26 At the same time, the results of the expression of intestinal MTTP are contradictory. A previous study conducted in humans showed no significant changes in intestinal MTTP expression in morbidly obese subjects with T2DM, 3 whereas other studies show that there is an increase in intestinal MTTP expression in a rabbit model of diabetes 27 and in insulin-resistant non-diabetic Zucker obese fa/fa rats. 28 However, there is little information regarding MTTP in humans.…”
Section: (Fas) (F) Apolipoprotein A-iv (Apo A-iv) (G) Diacylglyceromentioning
confidence: 88%
“…3 The mucosa was washed with physiological saline solution, scraped, immediately frozen in liquid nitrogen, and maintained at − 80°C until analysis. Other jejunal biopsies from the morbidly obese subjects group with low HOMA-IR were taken to isolate intestinal epithelial cells (IEC) (n = 6).…”
Section: Jejunal Biopsy Samplesmentioning
confidence: 99%
See 3 more Smart Citations